Candlenut shell as a lignocelullose raw material is a potential by-product for produce activated charcoal. It’s quality are affected by raw material and activated process i.e. temperature, activation time and activating agent. This paper intends to study the properties of activated charcoal made from candlenut shell. Candlenut shell was carbonization at 500 °Cfor 5 hour. Then activated using phosphoric acid in three different temperatures: 600 °C, 700 °C and 800 °C, in the duration time of 90, - Saptadi DARMAWAN; Gustan PARI; Kurnia SOFYAN (Departemen Hasil Hutan, IPB, 2009)
Candlenut shell as a lignocelullose raw material is a potential by-product for produce activated charcoal. It’s quality are affected by raw material and activated process i.e. temperature, activation time and activating agent. This paper intends to study the properties of activated charcoal made from candlenut shell. Candlenut shell was carbonization at 500 °Cfor 5 hour. Then activated using phosphoric acid in three different temperatures: 600 °C, 700 °C and 800 °C, in the duration time of 90, 120 and 150 minutes. The result shows that candlenut shell activated charcoal more influence of temperature than activation time. Overall, the activated charcoal met the Indonesian Standard requirement for commercialised activated charcoal with optimation activation at 800 °C for 120 minute. Keywords : Candlenut shell, activated charcoal, optimation, activation, phosphoric acid